Hip subluxation in Italian cerebral palsy children and its determinants: a retrospective cohort study. Issue 4 (5th September 2022) - Faccioli, Silvia; Sassi, Silvia; Ferrari, Adriano; Corradini, Elena; Toni, Francesca; Kaleci, Shaniko; Lombardi, Francesco; Benedetti, Maria Grazia
Abstract : The study's aim was two-fold: to describe the trend of hip subluxation in the largest sample of Italian nonambulatory cerebral palsy (CP) children ever published; to investigate its determinants. This single-centre retrospective cohort study included patients with spastic or dyskinetic CP, Gross Motor Function Classification System (GMFCS) level IV or V, age 0–18 years, having been referred to our unit before March 2020. The hip subluxation was measured by means of the migration percentage (MP). Other data were gathered such as sex, CP subtype, GMFCS level, presence of drug-resistant epilepsy, age, use of walkers with weight relief or standing devices, previous botulinum injection or hip surgery, oral or intrathecal baclofen and hip pain. Multiple linear stepwise regression was performed and descriptive statistics are provided. Spastic CP had MP maximum increase in early ages, with GMFCS level V values persistently higher than level IV. The dyskinetic subtype showed a slower increase of the MP, with GMFCS level IV presenting similar or higher values, compared to level V. Age, CP severity and spastic subtype are the main determinants. The stepwise multiple regression analysis demonstrated that weight relief walking and standing assistive devices, combined with botulinum contributed to reduce the MP progression. Dyskinetic CP showed overall lower MP values and a more variable behaviour relative to age and GMFCS level, compared to the spastic subtype. Standing and walking assistive devices, with partial or total weight relief, combined with individually targeted botulinum injections, should be considered in the management of bilateral nonambulatory CP patients, to prevent hip subluxation or its recurrence after surgery.